Pelatihan Modul Ajar Berbasis Pendekatan Culturally Responsive Teaching (CRT) Dalam Memperkuat Identitas Budaya Terhadap Guru dan Mahasiswa PPG Calon Guru di SMA Madani Palu - Nuraedah; Hasan; Windayanti; Mahfud M. Gamar; Suyuti (Jurnal Ragam Pengabdian, 2026)
Culturally Responsive Teaching (CRT)-based teaching module training plays a strategic role in fostering cultural sensitivity while strengthening the cultural identity of students and educators. This study aims to describe the process, results, and impact of CRT-based teaching module training for teachers and prospective teacher Professional Education (PPG) students at SMA Madani Palu. The method used is research and development (R&D) with a 4-D development model (define, design, develop, disseminate). Data were obtained through observation, in-depth interviews, questionnaires, and documentation, then analyzed descriptively qualitatively and quantitatively. The results of the study indicate that this training successfully produced teaching modules that are contextual and responsive to local cultural diversity, marked by an increase in participants' pedagogical competence, understanding of Kaili cultural values, and the ability to integrate local wisdom in learning. Evaluation through pre-test and post-test showed an average increase in the CRT concept understanding score of 28%, while the results of the module feasibility test by experts obtained an average score of 92% (very feasible category). These findings indicate that the CRT approach is not only effective in strengthening the cultural identity of teachers and PPG students as prospective teachers, but also enriches inclusive and relevant learning practices to the local context.